2023
DOI: 10.1071/cp21624
|View full text |Cite
|
Sign up to set email alerts
|

Whither digital agriculture in India?

Abstract: Agriculture is central to the Indian economy and suffers from widespread operational inefficiencies that could be corrected by the use of digital agriculture technologies (DA). We review and synthesise available literature concerning digital agriculture in India and anticipate its transformative potential in the coming decade. Although the initial growth of DA was more conspicuous in the downstream sectors and high-value crops, reaching smallholder farmers upstream is slowly emerging despite significant obstac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…This is the intended outcome of research policy in France and the EU to support digital agriculture (Bellon-Maurel et al 2023). The process is also implicit in the public-private partnerships reported for Australia (Hansen et al 2023;Lawes et al 2023) and in the digital agriculture start-ups observed in India (Goswami et al 2023). The openness of the public research process is seen as vital for the development of next-generation phenotyping (Tripodi et al 2023).…”
Section: Crop and Pasture Sciencementioning
confidence: 98%
See 4 more Smart Citations
“…This is the intended outcome of research policy in France and the EU to support digital agriculture (Bellon-Maurel et al 2023). The process is also implicit in the public-private partnerships reported for Australia (Hansen et al 2023;Lawes et al 2023) and in the digital agriculture start-ups observed in India (Goswami et al 2023). The openness of the public research process is seen as vital for the development of next-generation phenotyping (Tripodi et al 2023).…”
Section: Crop and Pasture Sciencementioning
confidence: 98%
“…Digital agriculture in such organisations may develop out of public sight, but may develop wherever the organisations are integrated vertically. For example, Goswami et al (2023) reports adoption by tech giants in Indian agriculture. Lawes et al (2023) reports the enabling effects of a vertically integrated data supply chain in Australian grains.…”
Section: Crop and Pasture Sciencementioning
confidence: 99%
See 3 more Smart Citations